Evaluation of the application of NPK liquid fertilizer on the growth performance and yield of the UBPR-6 rice line in shallow swampy areas - Sumardi, Sumardi; Chozin, Mohammad; Widodo, Widodo; Suprijono, Eko; Vadillah, Syavirah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Swamp land, especially shallow lowland swamps, has great potential and also has strategic value for the development of agricultural businesses, especially rice, to encourage the realization of a sustainable food self-sufficiency program. Fluctuations in water levels, which limit the application of fertilizer by spreading, can be reduced by the foliar fertilization method.  This research aims to evaluate the application of NPK liquid fertilizer on the growth performance and yield of the UBPR-6 rice line in shallow swampy areas. The experiment was carried out September 2022-January 2023 in shallow swampland at the Faculty of Agriculture, Bengkulu University. Using a Divided Plot design which places the NPK liquid fertilizer concentration (3.%, 6%, 9% and 12% as the main plot and application frequency (1, 2 and 3 times) as a subplot, with 3 replications. The results showed that high The plants were not affected by the application of liquid NPK fertilizer, but flowering accelerated along with increasing the concentration and frequency of fertilizer application. A concentration of 9% gave the best results with a yield of 3,505 kg per plot (6.25m2) or equivalent to 4.2 tons per hectare.